THE INFLUENCE OF MEDIA EXPOSURE, SAFETY AND HEALTH CONCERNS, AND SELF-EFFICACY ON ENVIRONMENTAL ATTITUDES TOWARDS ELECTRONIC GREEN PRODUCTS - Iman Khalid A. Qader; Yuserrie Zainuddin (Asian Academy of Management Journal, 2011)
As the high-tech industry evolves at a rapid pace, vast amounts of hazardous materials are used in fuelling its global expansion. These rapid changes in production processes are significantly depleting natural resources. With the surge of popular interest and awareness pertaining to environmental issues, organisations may be in peril if consumers’ attitudes towards their products are ignored. This study intends to understand consumers’ environmental attitudes towards electronic green products and to identify the effect of three factors, namely, media exposure, safety and health concerns, and self-efficacy, on this attitude. Data were collected via a self-administered questionnaire among 170 respondents in a public university. The results of the study indicated that safety and health concerns as well as self-efficacy had significant positive impacts on consumers’ environmental attitudes. Surprisingly, however, media exposure did not exhibit any significant influence on consumers’ environmental attitude. It is recommended that campaign and awareness projects focus on safety and health issues. Additionally, media should play a more active role in increasing environmental awareness among consumers.